2019
DOI: 10.4317/jced.55686
|View full text |Cite
|
Sign up to set email alerts
|

Apps for oral hygiene in children 4 to 7 years: Fun and effectiveness

Abstract: BackgroundNowadays apps in preschool age are largely used in learning improvement. The aim of this work was to test effectiveness of apps in improving oral hygiene in children patients aged from 4 to 7 years and evaluating correlation between parents educational attainment and children oral hygiene.Material and Methods100 patients aged from 4 to 7 years were randomly assigned by an external office in the study group (SG: 32 females, 18 males) and in the control group (CG: 28 females and 22 males). Plaque index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 16 publications
1
23
0
1
Order By: Relevance
“…Specific programs for improving awareness could be implemented using easy-to-use tools. Indeed, technologies have been found to be effective in increasing the motivation and awareness of patients [ 43 , 44 ], for example as health apps used to discourage incorrect habits and to encourage healthy behaviors and motivate people to work out or to comply with a balanced diet plan. In this regard, something could also be done to nudge the population towards regular self-inspections and dental visits [ 45 ].…”
Section: Future Outlookmentioning
confidence: 99%
“…Specific programs for improving awareness could be implemented using easy-to-use tools. Indeed, technologies have been found to be effective in increasing the motivation and awareness of patients [ 43 , 44 ], for example as health apps used to discourage incorrect habits and to encourage healthy behaviors and motivate people to work out or to comply with a balanced diet plan. In this regard, something could also be done to nudge the population towards regular self-inspections and dental visits [ 45 ].…”
Section: Future Outlookmentioning
confidence: 99%
“…Recommended intake of fluoride for primary prevention of caries is reported to be 0.05 to 0.07 mg F/Kg/day [ 6 ] and, when concentration is more than 1.5 to 4 mg/L as the World Health Organization (WHO) recommends, dental fluorosis occurs [ 7 ]. In this perspective, an important issue is to prevent the abnormal intake of fluoride in children and it has to be advised by parents and health care figures by paying attention to dental hygiene habits [ 8 ], to feeding and tap water drinking.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of mHealth on school children may also depend on age. In a recently published study on children of 4 to 7 years, Zotti et al 28 found mobile apps to be more effective, engaging and fun compared to verbal oral hygiene instructions. The higher trend observed in our study may partly be due to the personalized nature of the educational lectures, as students received individual level oral health education and motivation from a dental professional.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Strategies that can be implemented to improve user engagement with an app include ease of use, attractive user interface, unique smartphone features (eg, real-time visualized brushing instructions), and tailored design and information. 13,15,30,31 Nevertheless, as suggested by several recently published studies, 17,18,28 incorporating mobile apps with a standard oral hygiene program may be a more plausible approach for oral health promotion among adolescents than educational lectures alone such as via distance motivational tutoring by a dentist or an educator.…”
Section: Discussionmentioning
confidence: 99%